CircYTHDF1/miR-19b-3p/YTHDF1 axis contributes to pregnancy-induced hypertension development by enhancing vascular endothelial cell injury - Fangyun Wang; Qinping Yang; Xiaolan Wang; Yuyan Guo; Shunhe Lin (Hypertension in Pregnancy, 2024)
Objective The biological role of circ_0004858 (circYTHDF1) in pregnancy-induced hypertension (PIH) and the underlying mechanisms were unknown, and which were explored in this study.Methods ELISA was employed to detect the level of inflammatory cytokines and biochemical parameters; flow cytometry was employed to detect cell apoptosis; western blot and qRT-PCR were employed to examine expression level.Results The level of IL-1β, TNF-α, IL-6, TGF-β1, ET-1, and Ang-II were significantly elevated in the peripheral blood of PIH patients. The co-culture of HUVEC and CD4+ T cells isolated from the peripheral blood of PIH patients significantly elevated the apoptosis and expression level of NRF2/HO-1 but reduced the protein level of ferroptosis-related markers (GPX4, FSP, and CoQ10B) in HUVEC. Also, the expression of circYTHDF1 and YTHDF1 were markedly up-regulated in HUVEC co-cultured with CD4+ T cells isolated from PIH patients, but miR-19b-3p expression was markedly down-regulated, and the similar results were observed in Ang-II-treated HUVEC. Based on the predicted binding sites, the luciferase reporter assay confirmed the interaction between miR-19b-3p and circYTHDF1 or YTHDF1. The results of qRT-PCR and western blot further demonstrated that circYTHDF1 competitively bound to miR-19b-3p to up-regulate YTHDF1 in HUVEC. Functionally, deleting circYTHDF1markedly reduced ferroptosis and apoptosis in Ang-II-treated HUVEC, but both which were reversed by miR-19b-3p inhibitor, suggesting the involvement of circYTHDF1/miR-19b-3p/YTHDF1 axis in vascular endothelial cell injury in PIH.Conclusions This study may provide a novel insight into the pathogenesis of PIH as well as a new treatment strategy.